Didactic Value in Disney's Movie Turning Red - Sya'diah, Annisa (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2024)
This study analyzes the didactic value in the Turning red film by using a classification that divides it into: religious value, social value, moral value, and cultural value. Using qualitative descriptive s and an objective approach. The results of the study found that there were 15 data, points: 2 on religious values describing the Meilin family regarding their beliefs; 5 on social values describing the social behavior of the characters in the film; 5 on moral values regarding the good and bad actions of the characters; 3 on cultural values regarding the red panda ritual that the Meilin family underwent.Keywords: Animated movie, Didactic value, Turning Red movie